2022
DOI: 10.1136/bmj-2021-068465
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of physical activity interventions delivered or prompted by health professionals in primary care settings: systematic review and meta-analysis of randomised controlled trials

Abstract: Objective To examine the effectiveness of physical activity interventions delivered or prompted by primary care health professionals for increasing moderate to vigorous intensity physical activity (MVPA) in adult patients. Design Systematic review and meta-analysis of randomised controlled trials. Data sources Databases (Medline and Medline in progress, Embase, PsycINFO, CINAHL, SPORTDiscus, Sports Medicine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
62
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(65 citation statements)
references
References 76 publications
0
62
1
2
Order By: Relevance
“…Time spent sitting (sedentary time) is an independent risk factor for all cause mortality, cardiovascular disease, cancer, and type 2 diabetes 4. Kettle and colleagues reported no significant effect of primary care interventions on sedentary time, while Larsen and colleagues found that physical activity monitor based interventions were associated with a mean decrease of 9.9 min/day 79…”
Section: Broad Range Of Benefitsmentioning
confidence: 99%
See 4 more Smart Citations
“…Time spent sitting (sedentary time) is an independent risk factor for all cause mortality, cardiovascular disease, cancer, and type 2 diabetes 4. Kettle and colleagues reported no significant effect of primary care interventions on sedentary time, while Larsen and colleagues found that physical activity monitor based interventions were associated with a mean decrease of 9.9 min/day 79…”
Section: Broad Range Of Benefitsmentioning
confidence: 99%
“…8 Trials measuring physical activity with objective devices, such as accelerometers or wearable activity trackers, found no significant difference in MVPA between groups, while trials relying on self-reported activity showed an increase of 24 min/week in intervention groups. 7 In a previous meta-analysis, Larsen and colleagues found that interventions using physical activity monitors increased MVPA by 48.5 min/week. 9 But they judged this evidence to be ‘low certainty’ due to publication and small study biases.…”
mentioning
confidence: 99%
See 3 more Smart Citations